2019
DOI: 10.3390/ijerph16142549
|View full text |Cite
|
Sign up to set email alerts
|

Motivation in the Athens Classic Marathon: The Role of Sex, Age, and Performance Level in Greek Recreational Marathon Runners

Abstract: The aim of the present study was to examine the motivation of recreational runners and its variation by sex, age, and performance level. Finishers (female: n = 32, age 40.1 ± 9.0 years old, height 162 ± 7 cm, body mass 57.7 ± 7.5 kg, race record 4:34 ± 0:39 h:min; male: n = 134, 44.2 ± 8.6 years, 176 ± 6 cm, 77.0 ± 9.3 kg, 4:02 ± 0:44 h:min) in the Athens Classic Marathon 2017 completed the Motivations of Marathoners Scales (MOMS) 56-item questionnaire. The highest scores in the MOMS were observed in the gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 22 publications
5
55
2
Order By: Relevance
“…Investigated ultramarathon runners claim that regular training has a positive effect on physical and mental health and has a cleansing effect on the psyche. There is also some evidence from previous studies that running has a positive impact on mental health and causes feeling of catharsis [1,26]. Moreover, the satisfaction with one's running progress mediated relationships between well-being and the amount of running.…”
Section: Ultramarathons-from Extreme To Mainstream: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Investigated ultramarathon runners claim that regular training has a positive effect on physical and mental health and has a cleansing effect on the psyche. There is also some evidence from previous studies that running has a positive impact on mental health and causes feeling of catharsis [1,26]. Moreover, the satisfaction with one's running progress mediated relationships between well-being and the amount of running.…”
Section: Ultramarathons-from Extreme To Mainstream: Discussionmentioning
confidence: 92%
“…The dynamic development of mass sports events comes with questions about the motivations of the postmodern man to participate in them. Recently, researchers focused mainly on mass, popular, street runs/cycling events in the context of their meaning for sporting events and active tourism or in the context of motivation for running/cycling or health implications for runners/cyclists [22][23][24][25][26][27][28][29]. Sporting events have been analyzed as a tourist phenomenon [30][31][32][33][34] and the social identity of athletes is rarely investigated in this area.…”
Section: Ultramarathons-from Extreme To Mainstream: Discussionmentioning
confidence: 99%
“…Unfortunately, body mass was not available in these runners. Another explanation could be the motivation of female athletes [22]. For example, motivation differs between female and male marathon runners [22].…”
Section: Sex Difference In Performancementioning
confidence: 99%
“…Another explanation could be the motivation of female athletes [22]. For example, motivation differs between female and male marathon runners [22]. It has been shown that female marathon finishers exceeded men on the motivational scales for body weight concern, affiliation, psychological coping, life meaning, and self-esteem, and they scored lower on competitive motivation [23].…”
Section: Sex Difference In Performancementioning
confidence: 99%
“…Recent studies on ultra-marathons have indicated that whereas the rivalry factor has always been more important for men, it has also gained importance among women [25]. Recently partially confirmed that female and male marathon runners differ in their motivations [26]. Smith (2010) investigated the motivations of female elite triathletes [27], and Fernandez-Lopez et al [28] examined the relationship between sex and motivation in triathletes.…”
Section: Introductionmentioning
confidence: 99%